Essentials of company law - Ali Mohamed, Ashgar Ali; Venugopal, A. Vijayalakshmi; Ahmad, Muhamad Hassan; Ramalingam, Chithra Latha (LexisNexis Malaysia Sdn Bhd, 2025)
The law regulating the companies in Malaysia is the Companies Act 2016 (Act 777) (‘CA 2016the Act’) which had repealed the Companies Act 1965 (Act 125). Companies are classified as limited by shares, limited by guarantee, and unlimited liability companies. It can further be divided into public and private companies. The constitutional of the company is an important document which sets out the fundamental conditions of the company which would provide information to the shareholders, creditors and general public. A company limited by guarantee must have a constitution while for the other types of company, it is an optional. If the company has a constitution, the company, each director and each member of the company shall also have the rights, powers, duties and obligations as set out in the Act. Apart from the above, the Act prescribed the requirements of directors in a company, company secretary and the appointment of auditor as well as the procedures for the removal as well as their resignation. The winding up of a company either by way of a voluntary winding up or a compulsory winding up are is also featured in the Act. Having said the above, this chapter discusses some of the essential feature of the company law with reference to the Companies Act 2016.